2020
DOI: 10.1017/dmp.2020.244
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for Personal Protective Equipment in a COVID-19 Medical Shelter

Abstract: The coronavirus (COVID-19) has greatly impacted healthcare systems worldwide, leading to an unprecedented rise in demand for healthcare resources. In anticipation of an acute strain on established medical facilities in Dallas, Texas, federal officials worked in conjunction with local medical personnel to convert a convention center into a Federal Medical Station capable of caring for patients affected by COVID-19. A 200,000 square foot event space was designated as a direct patient care area, with surrounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Our study showed a significant drop in the total number of patients, as evidenced in many other studies, like Hartnett et al, Thornton et al, and Santana et al studies (see Figure 7). [14][15][16] The main difference in our setup from other studies like Li Juan 5,17,18 The nursing staff rota is similar in our and Quah et al's studies. 17…”
Section: Comparison With Other Studiessupporting
confidence: 73%
See 3 more Smart Citations
“…Our study showed a significant drop in the total number of patients, as evidenced in many other studies, like Hartnett et al, Thornton et al, and Santana et al studies (see Figure 7). [14][15][16] The main difference in our setup from other studies like Li Juan 5,17,18 The nursing staff rota is similar in our and Quah et al's studies. 17…”
Section: Comparison With Other Studiessupporting
confidence: 73%
“…Ideally, donning and doffing should be at the entrance and exit of staff, respectively. 5 We are not following any specific doffing guidelines, but other studies have shown the adherence to specific doffing guidelines as shown in the Hockaday et al's study. 5,19,20 Reuse of N95 masks with hydrogen peroxide is questioned in some studies.…”
Section: Mistakesmentioning
confidence: 83%
See 2 more Smart Citations
“… 8 9 In facilities where medical resources are relatively sufficient, a comprehensive precaution strategy, including a proper layout of the hospital, full personal protective equipment (PPE) sets and enhanced training on the medical staff, could be applied. 10 In peacekeeping field hospitals, however, the shortage of PPE and the difficulty in its resupply has imposed a huge strain on the healthcare service. In an effort to consume PPE rationally, we applied a new ‘appointment–triage–disinfection’ protocol in the hospital, which allowed us to flexibly adjust the number of healthcare workers on duty, depending on the appointment of patients.…”
Section: Discussionmentioning
confidence: 99%